Origin of Intramolecular Low‐Threshold Amplified Spontaneous Emission. Issue 12 (29th March 2021) - Wei, Qi; Duan, Ruihong; Zhang, Qi; Xie, Linghai; Xia, Ruidong; Yi, Yuanping; Léonard, Jérémie; Haacke, Stefan; Cabanillas‐Gonzalez, Juan; Qian, Yan; Huang, Wei
Abstract: Amorphous thin films from solution‐processable semiconductors are key materials for low‐cost and large area optoelectronics. Design rules toward novel amorphous compounds with outstanding light emission and light amplification properties require understanding of the intimate relation between chemical and electronic structure. Here, a series of compounds with tunable electronic transition characters of the lowest excited state, from local excited (LE), hybrid local charge‐transfer (HLCT) to charge‐transfer (CT) character is delicately designed. By deploying a combination of computational calculations and femtosecond‐transient absorption experiments, it is shown that pure LE states strongly coupled to high wavenumber vibrational modes favor to form a few dominant discrete vibrational levels and are essential for optical gain, whereas HLCT or CT states are preferably coupled to low frequency vibrational modes and form a large number of consecutive vibrational levels which lead to broad excited‐state absorption overwhelming stimulated emission. The results provide guidelines for the rational design of efficient organic laser materials. Abstract : The intramolecular low‐threshold amplified spontaneous emission (ASE) is highly correlated to the character of the lowest excited states. The pure local excited state favors ASE with discrete vibrational levels for efficient population inversion. The charge transfer state does not exibit ASE because its significant inter‐fragment geometry change causes large vibronic coupling in the low‐frequency region, difficult to form well‐resolved vibrational energy levels.